Immigration and acculturation in Brazil and Argentina : 1890-1929 - Bletz, May E. (Palgrave Macmillan, 2010)
Immigration and Acculturation in Brazil and Argentina is an exploration of questions of nationality in Buenos Aires, Rio de Janeiro and Ŝo Paulo, at the time when these cities were flooded with impoverished European immigrants. In this study, which examines fictional, journalistic and (pseudo)scientific texts of the period, the author argues that processes of representation and identity formation between national and immigrant groups have to be examined within the historical context of the host nations.